An AMOS Model for Examining the Factors Influencing the Development of China Cross-Border E-Commerce Comprehensive Pilot Areas - Hong-Dou Wang; Chun-Fang Zheng; Xu Xiao (Discrete Dynamics in Nature and Society)
Cross-border e-commerce has greatly promoted the development of China’s foreign trade, and the cross-border e-commerce comprehensive pilot area (CBECCPA, in brief) is the main form for promoting the development of cross-border e-commerce. The study aims to find out what factors and to what extent these factors affect the development of the CBECCPAs. Adopting the structural equation model analysis (AMOS) method and the data in 2017 of the 35 CBECCPAs set in the former three batches in China, the paper studies the effects of four main factors, including economic foundation, telecommunication network foundation, e-commerce logistics, and scientific and technological innovation, on the development of the CBECCPAs. The empirical results show that the economic foundation of the city where a CBECCPA locates has a vital impact, scientific and technological innovation has a quite important effect, e-commerce logistics has an important impact, and telecommunications network foundation has a slight influence on the development of CBECCPA. On the basis of empirically analysis results, it is suggested to strive to develop the cities’ economy, increase investment in scientific and technological development, attach importance to scientific and technological innovation, and perfect the urban logistics system. Some suggestions are put forward, such as to make great efforts to develop the economy sustainably, to encourage to scientific and technological innovation, and to improve the logistics system. It is meaningful for the construction and development of the fourth and fifth batches of CBECCPAs.